Novel edible coatings pretreatment for enhancing drying performance and physicochemical properties of cherry fruits during multi-frequency ultrasonic vacuum far infrared radiation — Radio frequency vacuum segmented combination drying - Zepeng Zang; Xiaopeng Huang; Guojun Ma; Fangxin Wan; Yanrui Xu; Qiaozhu Zhao; Bowen Wu; Hongyang Lu; Zelin Liu (Ultrasonics Sonochemistry)
To maximize the drying efficiency and physicochemical quality of cherry fruits while minimizing energy consumption, this study investigated the effects of novel edible coatings (sodium carboxymethyl cellulose (CMC-Na) and sodium alginate (SA)) pretreatment combined with multi-frequency ultrasonic vacuum far infrared radiation-radio frequency vacuum (MUSVFIR-RFV) segmented drying on the drying performance and physicochemical properties of cherries. Results demonstrated that MUSVFIR-RFV segmented drying combined with coating pretreatment reduced the drying time by 11.11 ∼ 25.93 % compared to single drying. At a moisture conversion point of 50 %, the process achieved optimal drying performance and energy efficiency. Remarkably, multi-frequency ultrasound outperformed single-frequency ultrasound in terms of energy transfer intensity and uniformity. Physicochemical quality analysis revealed that the combination of CMC-Na or SA coatings with MUSVFIR-RFV segmented drying significantly improved the retention of soluble solids, individual sugar, natural bioactive compounds, TPC, TFC, and antioxidant activities (DPPH, ABTS, and FRAP). Texture and sensory properties showed that the hardness and adhesiveness of coated cherries were reduced, while elasticity, chewiness, and cohesiveness were significantly enhanced. Cherries subjected to (CMC-Na)-(MUSVFIR-RFV) treatment achieved higher scores in texture, crispness, color, sweet taste, appearance, and aroma, with lower bitterness and off-odor, leading to an overall acceptance score of 9.2, which was significantly higher than that of the control. Hierarchical clustering and PCA analysis further validated that the integration of coatings with segmented drying effectively improved the physicochemical quality of dried cherries. The findings provide scientific evidence for the development of efficient drying technologies for cherry, substantiating the potential advantages of combining edible coatings with MUSVFIR-RFV drying in enhancing drying efficiency, quality, and sensory attributes of cherries.